Objective Validation of Perfusion-Based Human Cadaveric Simulation Training Model for Management of Internal Carotid Artery Injury in Endoscopic Endonasal Sinus and Skull Base Surgery. Issue 2 (29th December 2017) - Shen, Jasper; Hur, Kevin; Zhang, Zhipeng; Minneti, Michael; Pham, Martin; Wrobel, Bozena; Zada, Gabriel
Abstract: BACKGROUND: The emergence of minimally invasive endoscopic endonasal skull base surgery has necessitated reproducible and realistic simulators of rare vascular injuries. OBJECTIVE: To assess the face and content validity of an innovative perfusion-based cadaveric model developed to simulate internal carotid artery (ICA) injury during endoscopic surgery. METHODS: Otolaryngology and neurosurgery trainees attempted 3 consecutive trials of endoscopic control of a parasellar ICA injury, with standardized technical feedback. Time to hemostasis (TTH) and blood loss were trended. All participants completed validated questionnaires using a 5-point Likert scale to assess the domains of confidence gain, face validity, content validity, and curriculum applicability. RESULTS: Among all participants (n = 35), TTH and mean blood loss significantly decreased between first vs second attempt ( P = .005), and first vs third attempt ( P = .03). Following the first attempt, trainees experienced an average 63% reduction in blood loss and 59% reduction in TTH. In the quartile of most improved participants, average blood loss reduction was 1115 mL (84% reduction) and TTH of 259 s (84% reduction). There were no significant differences between trainees of varying postgraduate year or specialty. Average pre and postprocedural confidence scores were 1.38 and 3.16, respectively ( P < .0001). All trainees reported model realism, which achieved mean face validity 4.82 ± 0.41 and content validity 4.88 ± 0.33. CONCLUSION: The perfusion-based human cadaveric ICA injury model achieves high ratings of face and content validity across all levels of surgical trainees, and enables safe, realistic simulation for standardized skull base simulation and future curriculum development. Objective improvements in performance metrics may translate to improved patient outcomes.